Pengaruh Faktor Keuangan Terhadap Harga Saham: Studi Kasus pada Perbankan Konvensional di IDX Tahun 2021-2023 - Yanti, Yanti; Eny Purwaningsih (SKeTsa Bisnis (e-jurnal), 2024)
AbstractThe purpose of this research is to analyze the impact of the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), and Non-Performing Loan (NPL) on the stock prices of conventional banking entities listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. The independent variables used are the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), and Non-Performing Loan (NPL), while the dependent variable is the stock price, taken from the closing price on May 31 of the following year (t+1). The sample consists of 33 financial reports from companies with positive net income for three consecutive periods, resulting in a total of 99 data points that meet the research criteria for conventional banking entities listed on the IDX during the 2021-2023 period. This research employs a causal method with multiple linear regression analysis. Based on the findings, individually, the Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPL) have a negative impact on stock prices, while the Net Profit Margin (NPM) has no impact on stock prices. The Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), and Non-Performing Loan (NPL) collectively have a simultaneous impact on stock prices. AbstrakTujuan riset disini guna menganalisa dampak Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), dan Non-Performing Loan (NPL) pada harga saham entitas perbankan konvensional tercatat diBEI pada periode 2021-2023. Digunakan variabel independen Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), Non-Performing Loan (NPL), serta harga saham yang diambil dari harga penutupan (31 Mei t+1) sebagai variabel dependen. Terdapat 33 data sampel laporan keuangan perusahaan dengan kriteria laba bersih positif selama 3 periode berturut-turut, dengan total 99 data yang memenuhi kriteria sampel riset pada entitas perbankan konvensional tercatat diBEI selama 2021-2023. Metode riset ini berjenis kausalitas dengan uji analisa regresi linear berganda. Berdasar temuan pengujian secara individu LDR, CAR dan NPL berdampak negatif pada harga saham, NPM tidak ada dampak pada harga saham. Sedangkan LDR, CAR, NPM serta NPL memberikan dampak secara simultan pada harga saham.